2022
DOI: 10.1021/acs.nanolett.2c03789
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Realization of a Skyrmion Circulator

Abstract: Magnetic skyrmions are mobile topological spin textures that can be manipulated by different means. Their applications have been frequently discussed in the context of information carriers for racetrack memory devices, which on the other hand, exhibit a skyrmion Hall effect as a result of the nontrivial real-space topology. While the skyrmion Hall effect is believed to be detrimental for constructing racetrack devices, we show here that it can be implemented for realizing a three-terminal skyrmion circulator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The theoretical size of natural pores in (C 60 ) ∞ nanosheets (~2.1 Å) is much smaller than the kinetic diameters of common organic solvents (e.g. acetonitrile 3.4 Å, methanol 3.6 Å, hexane 4.3 Å, ethanol 4.5 Å) [5a,1213] , largely hindering the penetration of organic solvents. As reported previously, [6] polymeric C 60 crystals start to depolymerize when the temperature is higher than 500 °C.…”
Section: Resultsmentioning
confidence: 98%
“…The theoretical size of natural pores in (C 60 ) ∞ nanosheets (~2.1 Å) is much smaller than the kinetic diameters of common organic solvents (e.g. acetonitrile 3.4 Å, methanol 3.6 Å, hexane 4.3 Å, ethanol 4.5 Å) [5a,1213] , largely hindering the penetration of organic solvents. As reported previously, [6] polymeric C 60 crystals start to depolymerize when the temperature is higher than 500 °C.…”
Section: Resultsmentioning
confidence: 98%
“…The small nanosheets create more edge pores and shorten the lateral channels during their stacking compared with the large nanosheets, providing more perpendicular pathways to the membrane surface (Figure S12) . [12] The thickness of the porous (C 60 ) ∞ sheet membrane prepared with small (C 60 ) ∞ nanosheets is kept the same as that of the membrane with large (C 60 ) ∞ nanosheets. When the lateral size of the (C 60 ) ∞ nanosheets is reduced (Figure 3d), the flux of most of the studied solvents shows an increase.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, the SkHE was viewed as a harmful problem for devices, and great efforts were made to suppress it [18,19]. However, recent research has shown that the SkHE can be utilized to design various devices [16,[20][21][22][23][24][25][26][27][28][29]. For example, Hong et al take advantage of skyrmions' large transverse motion induced by SkHE-designed transistors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Whang et al proposed a fast and robust oscillator that utilizes the SkHE to modulate the skyrmion's movement [27]. Additionally, several diodes have been proposed and implemented using the SkHE-induced unidirectional transportation of skyrmions [24][25][26]29]. In other words, the SkHE can control the movement of the skyrmion when it performs different functions in devices.…”
Section: Introductionmentioning
confidence: 99%